Modern approaches to brain imaging in drug addiction (literature review) - D. V. Cheboksarov; M. V. Petrova; A. Yu. Simonova; O. V. Strunin; O. V. Ryzhova; A. K. Shabanov; S. S. Petrikov (Вестник анестезиологии и реаниматологии, 2023)
Background. Brain neuroimaging studies provided information about the neurobiological effects of narcotic substances, and established the mechanisms of their systematic use, as well as provided important information about the subjective experience and behavior of people with drug addiction, including their struggle for recovery. Until recently, five main methods of brain neuroimaging were considered – structural magnetic resonance imaging (MRI), functional MRI (fMRI), magnetic resonance spectroscopy (MRS), positron emission tomography (PET) and single-photon emission computed tomography (SPECT). These methods allow us to identify various aspects of the structure or function of the brain. Microwave thermometry (MR thermometry) is also used as a neuroimaging method of the brain, which allows us to study the temperature homeostasis of the brain in various human conditions.Materials and methods. The search for domestic publications was carried out in the database on the RSCI website, foreign – in the PubMed, Google Scholar databases in the period 1990–2022. When analyzing the PubMed database, the query «neuroimaging drug addiction» found 16066 links. We also studied works on the following keywords: «neurotransmitters and drug abuse». Publications describing the clinical picture, diagnosis, and poisoning with psychoactive substances were analyzed. A total of 45 articles were analyzed.Conclusion. The obtained results strongly confirm that drug addiction is a brain disease that causes important disorders in many areas, including pathways affecting encouragement and cognition. Neuroimaging methods allow researchers to observe the effect of drug substances on the brain and compare the structure, functions and metabolism of the brain in people who abuse and do not abuse drug’s substances. MR thermometry allows measuring the temperature of the brain, which is a reflection of the metabolism of the brain and allows assessing the effect of various substances on the brain. However, nowadays, there is not enough information about the change in cerebral temperature when using psychoactive substances.